Republic of Lithuania : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2011)
This Selected Issues Paper quantifies the variability of tax elasticities in Lithuania using two alternative methods: rolling regressions and pooled mean group estimator. The analysis is motivated by the systematic variation of tax revenues observed over the economic cycle. Both methods confirm that tax elasticities moved with the cycle, which can be attributed to the procyclical tax compliance tendencies and structural composition effects across tax bases. The results of the study emphasize the importance of accounting for cyclical variation in tax elasticities when making short-term tax revenue projections.